Group Counseling Services with Modeling Techniques to Increase Bullying Behaviour Awareness - Wiharto, Toni Wiet; Suriswo, Suriswo; Sudibyo, Hanung (Journal of English Language and Education, 2025)
Bullying behavior must be addressed not only for the perpetrators but also for the victims. School counselors can provide emotional and psychological support to victims of bullying, helping them recover from the trauma they have experienced. The objectives of this study are: 1) to determine the level of awareness of bullying behavior before, 2) and after the implementation of group counseling services using modeling techniques, and 3) to assess the effectiveness of group counseling services using modeling techniques in increasing awareness of bullying behavior. This research is experimental, with a population and sample of 20 students. The results showed that the level of awareness of bullying behavior before the implementation of group counseling services with modeling techniques was categorized as low, and after the implementation, it was categorized as high. Based on the t-test, group counseling services with modeling techniques were found to be effective in increasing awareness of bullying behavior among XI TKR 3 students of SMK Diponegoro Lebaksiu, Tegal Regency.